Vaksin HPV sebagai Strategi Pencegahan Kanker Serviks di Indonesia - Suryoadji, Kemal Akbar; Ridwan, Alifaturrasyid Syafaatullah; Kusuma, Fitriyadi (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2023)
Cervical cancer is the third most common cancer in women in the world and the second most common in women in Indonesia. Cervical cancer accounts for 7.5% of cancer deaths in the world and most of them come from developing countries including Indonesia. The cause of cervical cancer is high-risk HPV and can actually be prevented through high-risk HPV vaccines that are available throughout the world, including Indonesia. Discussion: The HPV vaccine has been shown to be effective in preventing cervical cancer, which is known to reduce the incidence by up to 90%. Various preparations of the HPV vaccine have been shown to be safe to give to patients. Conditions in Indonesia currently make the HPV vaccine a mandatory vaccine given as part of the school children's immunization month program as an effort to prevent cervical cancer for the community in the future. Conclusion: The HPV vaccine has effectiveness and side effects that are safe to be given to the public at large. The policy in Indonesia to require the provision of the HPV vaccine in the schoolchildren's immunization month program is the right step to prevent cervical cancer.